1991
DOI: 10.1115/1.2910573
|View full text |Cite
|
Sign up to set email alerts
|

Transient Laminar Mixed Convective Heat Transfer in a Vertical Flat Duct

Abstract: Transient Laminar Mixed Convective Heat Transfer in a Vertical Flat DuctUnsteady laminar aiding and opposing mixed convection heat transfer in a vertical flat duct is numerically investigated for an initially fully developed flow. Results indicate that unsteady heat transfer characteristics in the flow are principally determined by wall-to-fluid heat capacity ratios. Effects of the buoyancy and degree of asymmetric heating or cooling are rather insignificant. Correlation equations for the time variations of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…They showed that the axial diffusion of heat in the wall of a tube becomes negligible for the low values of the thermal report/ratio of conductivity solid-fluid or thicknesses of the wall. Lin et al [4] obtained a numerical solution for a unsteady laminar aiding and opposing mixed convection heat transfer in vertical flat duct. They indicated that unsteady heat transfer characteristics in the flow are principally determined by wall-to fluid heat capacity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the axial diffusion of heat in the wall of a tube becomes negligible for the low values of the thermal report/ratio of conductivity solid-fluid or thicknesses of the wall. Lin et al [4] obtained a numerical solution for a unsteady laminar aiding and opposing mixed convection heat transfer in vertical flat duct. They indicated that unsteady heat transfer characteristics in the flow are principally determined by wall-to fluid heat capacity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Approximation methods in which the thermal capacity of the pipe wall is assumed negligible were proposed by Siege1 (19601, Sucec (1975), and Li (1986). Based on the lumped capacitance approach to the transient heat conduction in the wall, Sucec (1981) and Lin (1991) obtained exact analytical and numerical solutions for a finite wall thermal capacity. Later, Lin and Kuo (1988) included the effect of the internal thermal resistance of the wall by using a one-dimensional (1-D) model of transient heat conduction in the radial direction.…”
mentioning
confidence: 99%